MORPHOMETRIC CHARACTERS OF MARINE LOCAL FISH (Harpodon sp.) FROM TARAKAN, NORTHERN BORNEO - Endik Deni Nugroho; Dwi Anggorowati Rahayu; Moh. Amin; Umie Lestari (The East Java Biological Society, 2015)
Tarakan sea waters have geographical circumstances and landscapes that supported the existence richness of fishes that abundant and diverse. There is local fish called Pepija or Lembe-Lembe, but biological studies on this fish most poorly known. This research is aimed to identify the morphological characters of Nomei (Harpodon sp.). Based on specific caharcter, morphometric, and meristric characters. Morphometrics analysis can be used to clustering and understanding relationship of taxa. Each species represented 10% samples of male and female from each type we found and measured 35 characters (in mm). The canonical, clustering and similarity were used. Based on determinant morphological characters species (pectoral fin length reaches or exceeds the initial dorsal fin, dorsal fin earlier than ventral fins), dendogram morphological characters, meristic characters, PCA grouping proved that Nomei fish from Amal and Juata as Harpo-don nehereus.